Laryngeal Mid-Cord Erythroleukoplakias: How to Modulate the Transoral CO(2) Laser Excisional Biopsy - Mora, Francesco (Cancers (Basel), 2020)
Background: The endoscopic appearance of glottic erythroleukoplakias is non-predictive of their histopathology, potentially ranging from keratosis to invasive squamous cell carcinoma (SCC). The aim of this study was to assess a comprehensive workup for the one-step diagnosis and treatment of mid-cord erythroleukoplakias, using CO(2) laser excisional biopsy. Methods: We evaluated 147 untreated patients affected by 155 mid-cord erythroleukoplakias submitted to excisional biopsy by subepithelial (Type I) or subligamental cordectomy (Type II), across two academic institutions. Patients were evaluated by preoperative videolaryngostroboscopy, pre- and intraoperative videoendoscopy with biologic endoscopy (narrow band imaging, NBI, or the Storz professional image enhancement system, SPIES), either with or without intraoperative saline infusion into the Reinke’s space. Adequacy of treatment was the primary outcome. Results: The histopathologic diagnosis was keratosis in 26 (17%) cases, squamous intraepithelial neoplasia (SIN1-2) in 47 (30%), carcinoma in situ in 21 (14%), and SCC in 61 (39%) patients. The adequacy of treatment across the entire cohort was 89%. The intraoperative saline infusion procedure, facing not clearly suspicious lesions, raised the adequacy of treatment from 60% to 90% (p = 0.006). Conclusions: Excisional biopsy by Type I–II cordectomies, after a comprehensive diagnostic workup, should be accepted as an adequate and cost-effective treatment of unilateral mid-cord glottic erythroleukoplakias.